2020
DOI: 10.1097/psy.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Somatic Symptoms in Children With a Chronically Ill Family Member

Abstract: Objective Somatization and functional somatic symptoms reflect conditions in which physical symptoms are not sufficiently explained by medical conditions. Literature suggests that these somatic symptoms may be related to illness exposure in the family. Children with a parent or sibling with a chronic illness may be particularly vulnerable to developing somatic symptoms. This study provides a systematic review of the literature on somatic symptoms in children with a chronically ill family member. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Parental illness is associated with a significantly higher risk for youth mental and physical health problems, poorer health-related quality of life (HRQoL), and social, educational and employment difficulties that persist well into adulthood [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, having a parent with a chronic illness is related to a significantly higher risk for internalizing problems (e.g., depressive, anxiety, and somatic symptoms), externalizing problems (e.g., aggressive and delinquent behaviors), lower life satisfaction, and loneliness [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Compared to peers, the youth of chronically ill parents are also at higher risk of affective dysregulation, stress-related somatic disorders, and weakened immune responses [ 3 , 5 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental illness is associated with a significantly higher risk for youth mental and physical health problems, poorer health-related quality of life (HRQoL), and social, educational and employment difficulties that persist well into adulthood [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, having a parent with a chronic illness is related to a significantly higher risk for internalizing problems (e.g., depressive, anxiety, and somatic symptoms), externalizing problems (e.g., aggressive and delinquent behaviors), lower life satisfaction, and loneliness [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Compared to peers, the youth of chronically ill parents are also at higher risk of affective dysregulation, stress-related somatic disorders, and weakened immune responses [ 3 , 5 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, having a parent with a chronic illness is related to a significantly higher risk for internalizing problems (e.g., depressive, anxiety, and somatic symptoms), externalizing problems (e.g., aggressive and delinquent behaviors), lower life satisfaction, and loneliness [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Compared to peers, the youth of chronically ill parents are also at higher risk of affective dysregulation, stress-related somatic disorders, and weakened immune responses [ 3 , 5 , 16 , 18 ]. Parental illness is also related to poorer family functioning, which is associated with more family conflicts, less cohesion, and reduced communication which, in turn, are associated with poorer youth adjustment [ 3 , 5 , 7 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found children whose parents had a diagnosis of IBS had significantly higher healthcare utilization rates, not just for gastrointestinal symptoms but also for a wide range of somatic symptoms, as compared to a control group of children whose parents were not diagnosed with IBS. It is perhaps not surprising, then, that a recent systematic review of 27 studies of children with a chronically ill parent concluded that parental illness is related to increased somatic symptoms in children [ 26 ]. The relationship between increased somatic symptoms in children with chronically ill siblings was mixed, further highlighting the concept of intergenerational transmission [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is perhaps not surprising, then, that a recent systematic review of 27 studies of children with a chronically ill parent concluded that parental illness is related to increased somatic symptoms in children [ 26 ]. The relationship between increased somatic symptoms in children with chronically ill siblings was mixed, further highlighting the concept of intergenerational transmission [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 10% of children have a parent with a chronic medical condition [1], and up to one in five experience parental mental illness [2]. Existing evidence has found that parental illness is associated with somatic symptoms [3] and internalizing problems, such as depressive and anxiety symptoms [1,4,5]. Studies have also shown that some adolescents experience benefit finding in relation to being a caregiver to an ill parent [6,7] and children with ill parents may experience increased maturity, strengthened family relations, and appreciation [8,9].…”
mentioning
confidence: 99%